Independent bank guarantees as protection against breach of contract in international trade - Schelenz, UIf (School For Advanced Legal Studies, 2026)
Independent bank guarantees are commonly used in international trade as protective means in order to ensure that the underlying obligation is properly fulfilled. These guarantees take a number of different forms and are often interlinked in one and the same major international transaction. It is essential for the participants to know about the operation of bank guarantees and to be aware of the risks involved. Frequently the parties' attention is taken up with negotiation of the substantive contract and insufficient time is allocated for consideration of the text of the guarantee. As an international businessman of a major company and former European counsel to Citibank emphasizes, 'there is a widespread but erroneous belief that employers never call these guarantees'. 1 Accordingly, insufficient effort is made to negotiate them and useful protective measures are not incorporated.